Changes in the Age of Maximum Productivity of Researchers in the 21st Century - Popovych, O.S.; Vashulenko, O.S.; Kostrіtsia, O.P. (Science and Innovation, 2021)
Introduction. The modern ideas concerning the dependence of the productivity of researchers on their age, which were formed in the last century, has become quite relevant given the changes in the organization and nature of research activities over the past few decades. Problem Statement. The study of this issue becomes especially relevant for the optimization of personnel policy in R&D institutions of Ukraine in connection with the undesirable changes in the age structure of researchers. Purpose. The purpose of this research is to study the dynamics of publication activity of a group of members of the National Academy of Sciences (NAS of Ukraine) who are working today (or worked in past) in R&D sector. Materials and Methods. Information base of research is the data of System Science Ukraine information and analytical systems, bibliography of researchers, the official statistic data of Ukraine, and conventional mathematical and statistical methods. Results. The changes in the publication activity of 126 full members and associate members of the NAS of Ukraine, who were born in 1920—1940, have been studied. It has been found that the maximum number of publications in the age group up to 30 years is reported only for 1.2% of the group; that in the age group from 30 to 34 years is reported for 16.7%, which corresponds to the Harvey Lehman results of the 1930s. At the same time, the maximum number of publications is 34.1 for age group from 35 to 39 years, 12% for the age group from 40 to 44 years, and 16% for age group from 45 to 49 years. The second increase in the number of publications is observed 5—10 years after the first peak, with the second peak sometimes exceeding the first maximum. Conclusions. Today, the age of greatest productivity of researchers has shifted by about 30 years. This is because of the fact that the dynamics of the researcher productivity is determined not only by age-related changes in the physiological capabilities of his/her body, but also the nature of work, which in modern science has changed dramatically as a result of increasing amount of R&D and engineering information, complexity of research methods and technologies, and spreading joint research.